A coefficient clustering analysis for damage assessment of composites based on pulsed thermographic inspection - Zhao, Yifan; Tinsley, Lawrence; Addepalli, Sri; Mehnen, Jorn; Roy, Rajkumar (Elsevier, 2016)
This paper introduces a coefficient clustering analysis method to detect and quantitatively measure damage occurring in composite materials using pulsed thermographic inspection. This method is based on fitting a low order polynomial model for temperature decay curves, which (a) provides an enhanced visual confirmation and size measurement of the damage, (b) provides the reference point for sound material for further damage depth measurement, (c) and reduces the burden in computational time. The performance of the proposed method is evaluated through a practical case study with carbon fibre reinforced polymer (CFRP) laminates which were subjected to a drop impact test with varying energy levels. A novel method for reducing an entire thermogram sequence into a single image is introduced, which provides an enhanced visualisation of the damage area.
Keywords: NDT; Thermography; Impact damage assessment; Delamination